Islamic Financial Literacy and Technological Innovation Among Millennial Women Micro-Entrepreneurs in Bandar Lampung - Ruslaini; Indupurnahayu Indupurnahayu; Qurroh Ayuniyyah; Immas Nurhayati (Jurnal Internasional Ekonomi Islam, 2026)
Objective: This study aims to examine the direct effect of Islamic financial literacy on women’s economic roles and its indirect effect, mediated by technological innovation, among millennial women micro-entrepreneurs in Bandar Lampung. Method: This study employs a quantitative approach using survey data collected from women micro-entrepreneurs. A total of 130 questionnaires were initially collected across Lampung Province, with 65 valid samples selected through purposive sampling based on specific criteria. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).  Result: The findings reveal that Islamic financial literacy has a positive and significant effect on technological innovation (β = 0.691, p < 0.001), while technological innovation has a strong positive effect on women’s economic roles (β = 0.703, p < 0.001). Islamic financial literacy also directly influences women’s economic roles (β = 0.211, p = 0.021), although the effect size is smaller. Additionally, technological innovation significantly mediates this relationship (indirect effect = 0.486, p < 0.001), with the model demonstrating strong explanatory power (R² = 0.745).  Implication: These findings suggest that policymakers and MSME development institutions should integrate Islamic financial literacy programs with digital capacity-building initiatives.  Originality or Novelty: This study highlights the mediating role of technological innovation in linking Islamic financial literacy to women’s economic roles, providing empirical evidence from millennial women micro-entrepreneurs in a developing regional context